Harmony Among the Nation’s People: Prophet Muhammad’s Political Measures in Fostering Unity - Muhammad Nasrulloh; Mohamad Zakky Ubaid Ermawan; Moh. Thoriquddin; Khoirul Anam (Balai Penelitian dan Pengembangan Agama Semarang, 2025)
During the Prophet Muhammad’s era, Medina was a plural society inhabited by diverse tribes, ethnicities, religions, and cultures, which carried the potential for social friction due to tribal fanaticism. This pluralism posed a significant challenge for the Prophet’s mission, as diversity could foster both tolerance and conflict. Accordingly, his political measures to harmonize the Medinan community hold critical relevance for managing plural societies in the contemporary era. This study employs a normative-theological library research approach, analyzing primary sources including the Qur’an, ḥadīth, and sīrah, supplemented by classical and contemporary exegeses. Such an approach is relatively rare, as it focuses on fostering unity among citizens, positioning this study strategically in scholarly discourse. The findings indicate that the Prophet managed societal diversity through social reconciliation, reinforcement of collective identity, and peace agreements. An emotional approach facilitated the reconciliation of the Aus and Khazraj tribes by establishing the Ansar identity and integrating them with the Muhajirin within the Muslim community framework. Furthermore, the Prophet implemented non-aggression agreements with Jewish communities and surrounding groups to maintain social stability. His principles of harmony were based on mutual assistance, protection, and empathy, which remain highly relevant for promoting national unity, preventing conflict, and reinforcing humanistic values as the foundation of peace in contemporary societies.